Nanoporous Structure of Bone Matrix at Osteoporosis from Data of Atomic Force Microscopy and IR Spectroscopy - A. A. Gaidash; L. N. Sinitsa; O. A. Babenko; A. A. Lugovskoy (Journal of Osteoporosis)
It was found that in an osteoporotic bone the fraction of nanosized pores decreases, the mineral phase amorphizes, hydrated shells around mineralized particles of the bone matrix thicken, and adhesion forces increase. This contributes to the formation of water clusters similar to bulk water clusters compared to the healthy bone tissue and leads to the accumulation of more viscous liquid with increased intermolecular interaction forces in the pores of the bone matrix. Given this, the rates of chemical reactions proceeding in the water phase of ultrathin channels of general parts of collagen fibrils decrease. Ultimately, nanopores of collagen-apatite interfaces lose, to a certain extent, the capability of catalyzing the hydroxyapatite crystallization.